The Algorithms of Social Media for Science Education to Cybercrime Reduced - Bayquni; Zulva, Eva Achzani (Postgraduate, University of Mataram, 2023)
The purpose of this paper is to describe how the algorithm of the social media platform as an effort of science and ethics education for the community to reduce criminal behaviour in cyberspace. The advantage of the internet as cyber media that can be enjoyed by the public is the easy and cheap way to access it. With the internet, everyone who accesses it can find out all the information from around the world. information from various parts of the world. The function of the internet can be education, information, and even entertainment. However, along with that, the use of the internet also needs vigilance for children who are its users. users. Because there are often adult sites that should not be visited by them. The participation and supervision of parents is very important in this case.becomes very important in this case.This study is theoretical with a qualitative descriptive method. The approach used is a literature study by searching for various relevant sources. The data sources are reputable and accredited scientific journals, academic papers, videos, books and other substantial sources. These sources will be carefully elaborated to obtain a structured academic description. The study found that there is a need to design algorithms for various social media platforms that can serve as media for science education. In addition, ethical content is needed to educate the public about virtual crime. Science and ethics content play a role in reducing the occurrence of cybercrime.